Vreugde en verdriet in die huis van Jakob - Krüger, Paul (HTS teologiese studies, 2008)
Happiness and lament in the house of Jacob The birth narrative in Genesis 29:31-30:24 is a coherent mini drama in its own right, although it is embedded in the patriarchal narratives and as such furnishes important background to the unfolding drama in Jacob's house. In this narrative, the reader is invited right into the intricate family relations of a dysfunctional polygamous marriage, where two rivals communicate with each other and their mutual husband by means of the names given at birth to their children and the children of their slave girls. This article focuses on the quest for happiness, which is evident in the births and name-giving in the house of Jacob. Although true happiness remains elusive, at the end both women receive their dues. God keeps a balance between the two contenders, but the birth of Rachel’s son calls for a resolution still to come. The text is thus left open ended.